Flaccid skin protects hagfishes from shark bites. Issue 137 (13th December 2017) - Boggett, Sarah; Stiles, Jean-Luc; Summers, Adam P.; Fudge, Douglas S.
Abstract : Hagfishes defend themselves from fish predators by releasing large volumes of gill-clogging slime when they are attacked. Slime release is not anticipatory, but is only released after an attack has been initiated, raising the question of how hagfishes survive the initial attack, especially from biting predators such as sharks. We tested two hypotheses that could explain how hagfishes avoid damage from shark bites: puncture-resistant skin, and a loose and flaccid body design that makes it difficult for teeth to penetrate body musculature and viscera. Based on data from skin puncture tests from 22 fish species, we found that hagfish skin is not remarkably puncture resistant. Simulated shark bites on hagfish and their closest living relatives, lamprey, as well as whole animal inflation tests, revealed that the loose attachment of hagfish skin to the rest of the body and the substantial 'slack volume' in the subcutaneous sinus protect hagfish musculature and viscera from penetrating teeth. While recent work has found evidence that the capacious subcutaneous sinus in hagfishes is important for behaviours such as knot-tying and burrowing, our work demonstrates that it also plays a role in predator defence.